Studi Komparasi Hasil Belajar IPS dengan Menerapkan Metode Role Playing dan Metode Ceramah Bervariasi dalam Pembelajaran IPS Siswa Kelas VII SMP Negeri 2 Jakenan Kabupaten Pati - Yulianto, Lilik; Tukidi, Tukidi (Universitas Negeri Semarang, 2020)
Based on the fact in the field that the students learning outcomes using a variety of lecturing methods on social science learning process are not yet completely successful. The aim of this research is to know the students learning outcomes comparison between role-playing method and lecturing methods on the social science learning process of first-grade students of junior high school 2 Jakenan Pati. The result of this study shows that there is significant differentiation in students learning outcomes in the experimental group compared control group. The effective observation result is on 16,58 range score which means being in a medium category and the control group is on 16,26 range score which means in a medium category too. Based on t-test results, the deviation score between the learning outcomes on the experimental group and control group is 3,249, a score of thing > t-table (3,249>2,397). The experimental group got increasing learning outcomes to range on 22,76 and 10,69 for the control group.